PERBEDAAN PERSEPSI ANTARA LUTHER KRANK DAN VIC FROHMEYER TERHADAP TRADISI NATAL DALAM NOVEL SKIPPING CHRISTMAS KARYA JOHN GRISHAM - Haryati Sulistyorini (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2010)
This paper entitled â€œDfferent Perception between Luther Krank and Vic Frohmeyer towards Christmas Tradtion in Grishamâ€™s Skipping Christmasâ€ is aimed at describing a phenomenon on Christmas tradition in Hemlock United States of America. The main problem is to discuss the different perception between Luther Krank as the main character and Vic Frohmeyer as the supporting charactertowards Christmas tradition. There arebthree kinds of approaches used, namely structural, sociological and cultural approaches. The result of analysis shows that the main different perception between Luther Krank and Vic Frohmeyer are refusal and support to the Christmas tradition. The difference is caused by their the basic personality which is influenced by the occupational status. Finally, their different perception is not always as a problem forever. Luther also belongs to round and dynamic character since she has a lot of efforts to skip Christmas and also undergoes changes at the end of the story. At the end of the story this problem can be solved by the other peripheral character, Blair.Key words : Character, Christmas Tradition, , cultura, lPerception,sociological